Experiential Tourism and Experiential Marketing: An Innovative Approach - Dieguez, Teresa (2020)
The present paper addresses the theme “Experiential Tourism and Experiential Marketing” under the scope of the economy of experiences. The word “experience” appears to be very abstract and difficult to conceptualize due to its complexity and dynamic nature. Several authors, namely Pine and Gilmore, studied the theme and develop “The Four Realms of an Experience” construct, finding that experience must be studied and worked taking in account several dimensions. The need to understand and evaluate the tourist experience, as well as to investigate how the tourist perceives his experience in the tourist context, resulted in different researchers coming from diverse areas, including the marketing area. In this sense, this study focuses on the concept of experiential marketing, explaining how it relates to the tourist experience, and how both can positively contribute to the tourism sector. The present investigation does not present empirical results, being only theoretical